Dialoške značilnosti pridižnega besedila - jezikoslovni vidik - Bizjak Končar, Aleksandra (Slavistična revija, 2017)
This article examines the dialogic aspects of homiletic discourse by using a linguistic model for the semantic description of a complete (clausal) sentence proposed by C. Cloran (1994) within the framework of the systemic functional theory of language (Halliday 1985). Based on the analysis of 50 contemporary television sermons, we identify the rhetorical units, such as commentary, reflection, generalisation, action, conjecture, question, and report, which reveal the dialogic nature of monologic texts. The first goal of the article is to describe the lexico- grammatical features of dialogically-oriented rhetorical units. The second goal is to reveal their semantic functions in sermonic discourse.
Keywords: dialog; pridige; retorična enota; sistemsko-funkcijska teorija; stavčna poved